2000
DOI: 10.1590/s0100-204x2000001200016
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação espectral de solos desenvolvidos em uma toposseqüência de diabásio e folhelho da região de Piracicaba, SP

Abstract: RESUMO -Este trabalho teve como objetivo estudar as alterações de solos desenvolvidos numa toposseqüência composta por diabásio e folhelho (Piracicaba, SP), e sua relação com os dados espectrais. Ocorrem na toposseqüência os solos Latossolo Roxo (LR), Latossolo Vermelho-Escuro (LE), Podzólico Vermelho-Escuro (PE), Litossolo (Li) e Aluvial (Al) dos quais foram coletadas amostras a três profundidades. Foram obtidos dados de reflectância bidirecional dessas amostras em laboratório com espectrorradiômetro na faixa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
6
0
6
Order By: Relevance
“…The sub-surface horizons of low pedogenic development (Horizons B incipiente and C) show a greater intensity of reflectance than the surface horizons. This is explained by the greater amount of silt (Table 1) in these horizons, as was also shown by Demattê et al (2000). Furthermore, Grove et al (1992) reported that the presence of feldspars and 2:1 clay minerals contribute to the greater intensity of reflectance (Figure 4).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The sub-surface horizons of low pedogenic development (Horizons B incipiente and C) show a greater intensity of reflectance than the surface horizons. This is explained by the greater amount of silt (Table 1) in these horizons, as was also shown by Demattê et al (2000). Furthermore, Grove et al (1992) reported that the presence of feldspars and 2:1 clay minerals contribute to the greater intensity of reflectance (Figure 4).…”
Section: Resultssupporting
confidence: 63%
“…However, it was also the region that had soils with higher clay and lower Fe 2 O 3 concentrations, due to the predominant source materials being claystone and siltstone. The absence of opaque minerals enables the high intensity of reflectance, although the intensity of reflectance is medium-high in all profiles, indicating that higher levels of clay have a lower intensity of reflectance and those with higher levels of the silt have a higher intensity of reflectance, as shown by Demattê et al (2000) and Mathews et al (1973). The region has soil surface horizons with high organic matter content, resulting in a lower intensity of spectral reflectance and smoothing the concave feature of iron oxides (850-900 nm).…”
Section: Resultsmentioning
confidence: 77%
“…Existe um número razoável de trabalhos que utilizam sensores terrestres para o estudo do comportamento espectral de solos tropicais (Demattê & Garcia, 1999;Vitorello & Galvão, 1999;Demattê et al, 2000a).…”
Section: Introductionunclassified
“…In the bands from 2,100 to 2,200 nm (Viscarra Rossel, 2011; Demattê et al, 2016), valleys that are characteristic of kaolinite (Kt) were observed in the spectral curves, and, in the band at 2,265 nm (Demattê et al, 2000;Pizarro et al, 2001), valleys that are typical of gibbsite (Gb). All the studied soils showed valleys in the spectral curves that are characteristic of Kt (Figure 1), but only some had valleys characteristic of Gb.…”
Section: Resultsmentioning
confidence: 99%